2018
DOI: 10.15406/joentr.2018.10.00345
|View full text |Cite
|
Sign up to set email alerts
|

Speech in noise: hearing loss, neurocognitive disorders, aging, traumatic brain injury and more

Abstract: In this article, we explore and report the prevalence of speech in noise difficulties across multiple patient populations and reveal and speculate on management of the same. Speech in Noise problems is commonly associated with sensorineural hearing loss. The inability to understand speech in noise is often associated with, and attributed to, sensorineural hearing loss. However, some 12-15% of adults with normal hearing thresholds (i.e., pure tones) have difficulty hearing and struggle to understand speech in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…The research literature reveals many studies have reported patients' complaints of HDs in the presence of normal thresholds in 10 to 50% of their subjects, especially in older persons (e.g., Saunders and Haggard, 3 ; Gates et al, 4 Chia et al, 5 Hannula et al, 6 Tremblay et al, 7 Spankovich et al 8 ) Clearly, HDs and SIN problems are not limited to abnormal audiometric thresholds. According to Beck, Larsen, and Bush, 9 people with hearing thresholds WNLs may have supra-threshold auditory deficits due to or associated with any of the following: central presbycusis, auditory disability with normal hearing, obscure auditory dysfunction (OAD), King-Kopetzky Syndrome, auditory dysacusis, auditory processing disorders (APDs), idiopathic discriminatory dysfunction, hidden hearing loss (HHL), cochlear synaptopathy (CS), tinnitus, neurocognitive disorders, dyslexia, attention deficit disorder (ADD), attention deficit hyperactivity disorder (ADHD), traumatic brain injury (TBI), spatial hearing disorders (SHDs), aging, dementia, cognitive decline, presbycusis (sensory, neural, synaptic, auditory fiber, and/or central causes), noise-induced hearing loss (NIHL), mild cognitive impairment (MCI), receptive aphasia, and Alzheimer's Disease among others.…”
Section: Best Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The research literature reveals many studies have reported patients' complaints of HDs in the presence of normal thresholds in 10 to 50% of their subjects, especially in older persons (e.g., Saunders and Haggard, 3 ; Gates et al, 4 Chia et al, 5 Hannula et al, 6 Tremblay et al, 7 Spankovich et al 8 ) Clearly, HDs and SIN problems are not limited to abnormal audiometric thresholds. According to Beck, Larsen, and Bush, 9 people with hearing thresholds WNLs may have supra-threshold auditory deficits due to or associated with any of the following: central presbycusis, auditory disability with normal hearing, obscure auditory dysfunction (OAD), King-Kopetzky Syndrome, auditory dysacusis, auditory processing disorders (APDs), idiopathic discriminatory dysfunction, hidden hearing loss (HHL), cochlear synaptopathy (CS), tinnitus, neurocognitive disorders, dyslexia, attention deficit disorder (ADD), attention deficit hyperactivity disorder (ADHD), traumatic brain injury (TBI), spatial hearing disorders (SHDs), aging, dementia, cognitive decline, presbycusis (sensory, neural, synaptic, auditory fiber, and/or central causes), noise-induced hearing loss (NIHL), mild cognitive impairment (MCI), receptive aphasia, and Alzheimer's Disease among others.…”
Section: Best Practicesmentioning
confidence: 99%
“…Hearing aids, particularly those coupled to RMs, can help these individuals, even in the presence of thresholds WNL. 9,34 Many blast-exposed veterans complain of difficulty understanding SIN, rapid speech, and following instructions, often disproportionately to their peripheral hearing sensitivity. 35 FM and RM systems using Bluetooth are effective interventions for blast-exposed veterans with normal or near-normal hearing sensitivity, but HDs.…”
Section: Remote Microphone Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies have suggested several possible interventions for patients with abnormal auditory abilities, including compensatory strategies, counseling, and auditory training [ 13 ]. Several studies suggest that technologies that increase the signal-to-noise ratio (SNR), such as low- (or mild-) gain hearing aids (LGHAs), with or without the use of remote microphones, can provide significant benefits to those with SHDs and NHTs [ 14 , 15 , 16 , 17 ]. Anecdotal results from military audiologists have reported positive results from the use of LGHAs (i.e., self-reported satisfaction and use through data logging), and many military clinics have started routinely prescribing LGHAs to patients who present with SHDs and NHTs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the causes of hearing loss are well-established, the existing literature indicates that adopting behaviors to safeguard hearing health is challenging for individuals [ 2 , 14 ]. As reported, 46.7% of American adults aged 18 years and older have reported some degree of hearing difficulty [ 15 ].…”
Section: Introductionmentioning
confidence: 99%